2018
DOI: 10.3103/s1063457618040056
|View full text |Cite
|
Sign up to set email alerts
|

Nano Periodic Structure Formation in 4H–SiC Crystal Using Femtosecond Laser Double-Pulses

Abstract: Nano periodic structure formation in 4H-SiC crystal using femtosecond laser double-pulses The photo-induced periodic nano structure inside 4H-SiC have been induced by a femtosecond double pulse train. The alignment of the periodic structure is in the direction independently from crystal orientation. In particular, FE-SEM analysis revealed that the periodic structure on the fractured surface can be classified into two categories of the polarization-dependent and polarization-independent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Further details are actively under discussion. Research regarding the crystal state of LIPSS still continues, [7][8][9][10] and we have previously reported that it depends on the irradiated material. 7) Previous published literature shows that the period of LIPSS changes depending on a number of factors including, the number of superimposed laser pulses, 11,12) laser energy fluence, 4,13,14) laser scanning rate, 15) laser wavelength, 14,[16][17][18][19] and irradiated material.…”
mentioning
confidence: 99%
“…Further details are actively under discussion. Research regarding the crystal state of LIPSS still continues, [7][8][9][10] and we have previously reported that it depends on the irradiated material. 7) Previous published literature shows that the period of LIPSS changes depending on a number of factors including, the number of superimposed laser pulses, 11,12) laser energy fluence, 4,13,14) laser scanning rate, 15) laser wavelength, 14,[16][17][18][19] and irradiated material.…”
mentioning
confidence: 99%
“…Therefore, it has been chosen as the substrate for the samples used in this study. We investigated the crystallinity of the LIPSS by Synchrotron high-energy x-ray diffraction (XRD), through a correlation with crystallographic analysis of transmission electron microscope (TEM) observation [38][39][40][41] .…”
mentioning
confidence: 99%